Entrepreneurship, innovation and sustainability - Wagner, Marcus, 1973- (Greenleaf Pub., 2012)
This book addresses the intersection of entrepreneurship, innovation and sustainability (EIS), presenting high-quality research illuminating the relationship between the three fields.